PENGAMBILAN KEPUTUSAN DALAM KEADAAN RISIKO UNTUK PENENTUAN JUMLAH PRODUKSI - Widiyanto Tri Handoko; Antono Adhi (Jurnal Ilmiah Dinamika Teknik, 2010)
The concept of risk can be linked to uncertainties associated with events. Within the context of a project, risk is commonly associated with an uncertain event or condition that, if it occurs, has a positive or a negative effect on the project’s objectives or results in unwanted consequences. To complete the analysis of risk, the probability of each scenario is determined along with the magnitude or severity of the consequences involved. Additionally, there is uncertainty associated with each of these parameters that must also be evaluated. On a production planning, manager should predict how many product should be produced so we got the optimum profit when that produced sold to customer. Sometimes we got little profit or maybe loss, sometimes big profit when the rest of the product sold under production cost. With decision making in risk condition, we can reduce loss of profit.   Keywords: Decision Making, Risk Condition, Probability